Quantification of the Cannabinoid Type 1 Receptor Availability in the Mouse Brain - Miederer, Isabelle; Wiegand, Viktoria; Bausbacher, Nicole; Leukel, Petra; Maus, Stephan; Hoffmann, Manuela A.; Lutz, Beat; Schreckenberger, Mathias (Frontiers in Neuroanatomy, 2020)
The endocannabinoid system has been shown to be involved in a number of diseases such as addictive disorders, schizophrenia, post-traumatic stress disorder and eating disorders. As often mice are used as the preferred animal model in translational research, in particular when using genetically modified mice, the aim of this study was to provide a systematic analysis of in vivo cannabinoid type 1 (CB1) receptor ligand binding capacity by means of positron emission tomography using the ligand [18F]MK-9470. We then compared the positron emission tomography (PET) results with literature data from immunohistochemistry to review the consistency between ex vivo protein expression and in vivo ligand binding. Six male C57BL/6J (6 – 9 weeks) mice were examined with the cannabinoid type 1 receptor ligand [18F]MK-9470 and small animal PET. Different brain regions were evaluated using the parameter %ID/ml. The PET results of the [18F]MK-9470 accumulation in the mouse brain were compared with immunohistochemical literature data. The ligand [18F]MK-9470 was taken up into the mouse brain within five min after injection and exhibited slow kinetics. It accumulated highly in most parts of the brain. PET and immunohistochemistry classifications were consistent for most parts of the telencephalon, while brain regions of the mesencephalon and rhombencephalon were rated higher with PET than immunohistochemistry. This preclinical [18F]MK-9470 study demonstrated the radioligand’s applicability for imaging the region-specific CB1 receptor availability in the healthy adult mouse brain and thus offers the potential to study CB1 receptor availability in pathological conditions.